Strategi Kepemimpinan Instruksional Kepala Sekolah dalam Meningkatkan Mutu Pembelajaran IPA di SMP IT Al Qudwah Musi Rawas - Erni Wibowo; Episiasi; Donni Pestalozi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to describe and analyze the principal’s instructional leadership strategies in improving the quality of science learning at SMP IT Al Qudwah Musi Rawas. The research used a qualitative approach with a case study design. Data were collected through questionnaires, in-depth interviews, and documentation involving the principal and science teachers. The results show that the principal implements instructional leadership strategies through five main dimensions: setting the mission through the vision of deep learning; managing the instructional program through routine clinical supervision and random classroom visitations; developing a learning climate through STEM-based programs and learning communities (lesson study); managing learning facilities by prioritizing laboratory budgets and utilizing a natural laboratory; and integrating the distinctive values of Integrated Islamic Schools through the ADLX integrated approach and the internalization of ayat kauniyah. In conclusion, effective instructional leadership contributes to improving teacher discipline, enhancing students’ learning motivation, and strengthening the school’s quality identity through the integration of science learning and Islamic values. Keywords: Integrated Islamic School, Instructional Leadership, Science Learning Quality